Foyle's war revisited [videorecording (DVD)] - Allen, Dennis (Motion picture producer) ([Acorn Media], 2015)
Go behind the scenes of the series that has captivated viewers for more than a decade. Learn about the creation of Foyle's war, the decision to set it during World War II, the research that goes into each episode and the casting of Michael Kitchen as DCS Foyle.